Topology and Control Strategy of Power Electronic Traction Transformer for High Power Vehicle - ZHAO Lu; GE Qiongxuan; LI Yaohua (Kongzhi Yu Xinxi Jishu)
With the growing requirments of size and weight of converter in rail transit, high-power vehicle power electronic traction transformer(PETT) is one option to meet the miniaturization and lightweight trend of traction and driving system in high speed train. In this paper, topology of the power electronic transformer circuit for 25 kV single-phase power supply system was designed. Resonant PR controller was used to realize the unit power factor operation, and adaptive equalization control strategy of capacitor voltage and output power were realized based on the module voltage ranking method. Effectiveness of the proposed circuit topology and adaptive voltage equalization algorithm were verified by constructing the PSIM simulation system of 25 kV/4.5 MVA single-phase power electronic traction transformer, and the harmonic of the network current was analyzed.